Thermal performance optimization of heat pipe using nanofluid: response surface methodology - Gupta N.K.; Sharma A.; Rathore P.K.S.; Verma S.K. (My University, 2025)
Nanofluids are the new class of thermo-fluidics. Researchers found that nanofluids have the potential to enhance the thermal performance of various thermal applications. In the present paper, parametric optimization of the thermal performance of nanofluid-filled heat pipe is performed using response surface methodology. The operating parameters like power input, inclination angle, filling ratio of nanofluid (working fluid) and nanofluid concentration are considered. Optimization study predicted the optimum value of thermal efficiency, thermal resistance and wall temperatures as 66.40%, 0.3884 °C/W and 78.86 °C, respectively, at 112 W power input, 55% filling ratio, 1.1% nanofluid concentration and at 58.5° inclination angle. The predicted and experimental optimization results are in good agreement. © 2020, The Brazilian Society of Mechanical Sciences and Engineering.